Facial reconstruction: Validation of the Tedeschi-Oliveira method for estimating the pronasale point in Brazilians - Raíssa Ananda Paim STRAPASSON; Rodolfo Francisco Haltenhoff MELANI (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Forensic facial reconstruction aids in the process of human identification by facial recognition. The nose plays an important role in this process; however, its soft tissues wither away during cadaveric decomposition. There are few studies in the area of facial recognition of the Brazilian population, especially concerning Brazilian nasal prediction guides. This study aimed to test the hypothesis that the angle formed by the tangents drawn from the rhinion and prosthion points (nose tip) is equal to 90º, as proposed by the pioneer study by Tedeschi-Oliveira et al. (2016). It is important to highlight that this is the only method to date developed to predict the nasal tip in Brazilians, and has not yet been tested in other populations. Images of computed tomography scans of 228 individuals (171 females and 57 males) were screened according to the same criteria used by the authors of the primary study. The images were analyzed using the Horos® program, version 1.1.7 - 64 bit. The mean angle studied was about 90º, and any difference between this mean and the real angle measured did not significantly compromise the accuracy of the nose tip location. The findings tested in the present study corroborate the hypothesis investigated by Tedeschi-Oliveira et. al. Therefore, we suggest that the method be used in forensic practice to estimate nose tips in Brazilians.